Living in a Silver Zone: Residents' perceptions of area-wide traffic calming measures in Singapore. (December 2022) - Chng, Samuel; Chang, Catherine; Mosquera, Karenza; Leong, Wai Yan
Highlights: Q methodology was used to understand the lived experiences of traffic calming in Singapore. We found three perspectives: Road Safety Enthusiast, Inconvenienced Users, and Implementation Critics. The lived experiences and perceptions of the traffic calming measures were different across groups. The benefits and inconveniences of these measures were felt differently across these groups. The efficacy of Q methodology for mobility and planning related research is supported. Abstract: Traffic calming has been introduced in many cities in a bid to create more age-friendly and sustainable communities. This study uses Q methodology to understand the perspectives and experiences of residents after almost a decade since the first implementation of traffic calming measures in neighbourhoods in Singapore. In particular, we focused on the Silver Zone programme, which involves the introduction of senior-friendly road safety features in areas with a high proportion of senior residents and where there have been past road traffic injury involving seniors. With 26 participants, we identified three perspectives and termed them the Road Safety Enthusiast, Inconvenienced Users, and Implementation Critics. While their perspectives of the traffic calming measures were different, we found that all three groups broadly supported the objectives of Silver Zones. The participants were able to identify that the benefits of traffic calming go beyond protecting vulnerable populations to enhancing the liveability and overall traffic safety of their neighbourhood and community. However, the benefits and inconveniences of these measures were felt differently across these groups, which are areas for planners and policymakers to address to increase the support for traffic calming in neighbourhoods. The efficacy of Q methodology for mobility and planning related research is also supported and further discussed in the article.